The long-term impact of engaged scholarship: How do SMEs capitalise on their engagement with academics to explore new opportunities?. (June 2018) - Rosli, Ainurul; de Silva, Muthu; Rossi, Federica; Yip, Nick
We investigate whether – and how – small and medium-sized enterprises (SMEs) are able to capitalise on their engagement with academics in order to explore new opportunities beyond the achievement of the immediate objectives of their collaboration. Using empirical evidence drawn from academic–SME collaborations supported by the Knowledge Transfer Partnership programme in the United Kingdom, we find that for many SMEs, engagement with academics has led to new business opportunities, including new market creation, new project engagement, new venture creation and new strategic network development. The exploration of new business opportunities is facilitated when three overarching factors are present: (1) a capable boundary spanner, who creates bridges within the SME and between the SME and the university, and gains an in-depth knowledge of the collaboration's content; (2) a committed SME leadership willing to allocate resources and permissions to the collaboration, and encouraging an open flow of communication; (2) a strong relationship, characterised by trust and cognitive proximity, between the collaboration's partners, who engage in open discussions and acknowledge and respect their different roles and responsibilities. These findings offer suggestions to SMEs, universities and policymakers in relation to improving the generation of long-term impacts on SMEs through engaged scholarship.